2012
DOI: 10.1098/rspa.2012.0279
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural level response of HMX–Estane polymer-bonded explosive under effects of transient stress waves

Abstract: The effect of transient stress waves on the microstructure of HMX-Estane, a polymerbonded explosive (PBX), is studied. Calculations carried out concern microstructures with HMX grain sizes on the order of 200 mm and grain volume fractions in the range of 0.50-0.82. The microstructural samples analysed have an aspect ratio of 5 : 1 (15 × 3 mm), allowing the transient wave propagation process resulting from normal impact to be resolved. Boundary loading is effected by the imposition of impact face velocities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…This indicates the possibility of force chains in the material, and there might be some crystals that form favorable paths for the load transfer mechanism. The speculated force chains are based on the continuity of the compressive strain across the specimen length, and are in crystals either in contact or very close to each other, which agrees well with the fact that as the solid loading increases it results in permanent stress bridging [28]. However considering the percentage of solid loading used in the specimen, additional work is needed at different solid loadings to reach a conclusive observation on the force chain formation in the material.…”
Section: Mesoscale Deformation Behaviorsupporting
confidence: 71%
“…This indicates the possibility of force chains in the material, and there might be some crystals that form favorable paths for the load transfer mechanism. The speculated force chains are based on the continuity of the compressive strain across the specimen length, and are in crystals either in contact or very close to each other, which agrees well with the fact that as the solid loading increases it results in permanent stress bridging [28]. However considering the percentage of solid loading used in the specimen, additional work is needed at different solid loadings to reach a conclusive observation on the force chain formation in the material.…”
Section: Mesoscale Deformation Behaviorsupporting
confidence: 71%
“…(4.1) in Ref. 46. For a grain volume fraction of 0.95, such as that used in PBX9501, the average stress is predicted to be $457 MPa, which is within 3.3% of the value obtained from experiments.…”
Section: Large Samples Without Wave Reflectionsmentioning
confidence: 52%
“…In Ref. 46, the authors quantified the evolution of fracture energy. An analysis of the spatial distribution of fracture energy showed that the maximum fracture dissipation occurs near the impact face and gradually decreases to zero at the front of the stress wave.…”
Section: Large Samples Without Wave Reflectionsmentioning
confidence: 99%
“…Reaugh et al [10] developed a high explosive response to the mechanical stimulus model (HERMES) by simultaneously considering the yield strength, the equation of state, particle fractures, and so on, and also built up the relationship between cracks and ignition. However, because these models could not describe the microstructural effect of PBXs, Barua and Zhou [11] and Barua et al [12][13] developed a Lagrangian framework based on the cohesive finite-element method to analyze the crack evolution of the interface between the explosive crystal and polymer and further the ignition induced by the shock wave generated from the high-velocity impact, in view of the PBX microstructure. Although these works revealed that the hot-spot formation was initiated by microcracks, how the stochasticity of the microcracks affected hot-spot formation was not quantified in detail.…”
Section: Introductionmentioning
confidence: 99%